A steep peripheral ring in irregular cornea topography, real or an instrument error? - Galindo-Ferreiro, Alicia; Galvez-Ruiz, Alberto; Schellini, Silvana A. [UNESP]; Galindo-Alonso, Julio (Wolters Kluwer, 2016)
Purpose To demonstrate that the steep peripheral ring (red zone) on corneal topography after myopic laser in situ keratomileusis (LASIK) could possibly due to instrument error and not always to a real increase in corneal curvature. Methods A spherical model for the corneal surface and modifying topography software was used to analyze the cause of an error due to instrument design. This study involved modification of the software of a commercially available topographer. Results A small modification of the topography image results in a red zone on the corneal topography color map. Conclusion Corneal modeling indicates that the red zone could be an artifact due to an instrument-induced error. The steep curvature changes after LASIK, signified by the red zone, could be also an error due to the plotting algorithms of the corneal topographer, besides a steep curvature change.
Keywords: Irregular corneal astigmatism; Red zone; Spherical aberration; Topography